MODEL INTEGRASI PELAJARAN AGAMA DAN PELAJARAN UMUM DI SEKOLAH ISLAM TERPADU SALSABILA GROUP - Hozaimi (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This article was written to describe the model of integrating religious (Islamic) lessons with general lessons at the Salsabila Group Integrated Islamic School under the auspices of the Salsabila Islamic Education Institute (LPI), the Indonesian Child Lovers Silaturrahim Foundation (SPA). LPI Salsabila houses six (6) PAUD level schools, eight (8) elementary school level schools, and two (2) middle school level schools. These schools are spread across various regions, namely Magetan, Klaten, Sleman, Yogyakarta City, Bantul, Purworejo, Magelang, and West Kutai. The approach used in this research is a qualitative approach. Data collection was carried out through observation, interviews and documentation review. The procedures carried out in the data analysis process are data collection, data reduction, data presentation, and drawing conclusions. The data validity test was carried out using credibility and confirmability tests. The research results show that Islamic religious lessons at the Salsabila Group Integrated Islamic School include Tahsin Al Qur'an and Tahfidz Al Qur'an and the habit of noble morals based on the sunnah. The integration of Islamic lessons with general lessons (national curriculum) is carried out in the following ways, namely (1) integrated curriculum, Islamic lessons (Tahsin and Tahfidz Al Qur'an) as local content in the national curriculum structure, (2) integrated days, Al Qur'an lessons 'an is carried out in an integrated manner on the same day, and (3) integrated learning, namely integrating verses from the Qur'an and Hadith of the Prophet SAW into related learning topics.